Regulation Of Macrophage Cellular Response By Clinacanthus Nutans Extracts In J774.2 Macrophage Cell Line - Mohamed, Nur Mazidah Haji Noor (2019)
Clinacanthus nutans, which is a medicinal plant from Acanthaceae family, is well-known as 'Belalai gajah' and Sabah Snake Grass in Malaysia. C. nutans extracts have been reported to exhibit anti-inflammatory, analgesic, anti-oxidant, anti-cancer, anti-viral and anti-bacterial properties. However, the effects of C. nutans extract towards the immune system and its immunomodulatory capabilities have not been well explored until today. Macrophage activation, which is necessary to elicit an immune response, is lacking in certain macrophage related immunodeficiency cases whereas macrophage activation occurs constitutively in certain inflammatory diseases. Thus, the immunomodulatory roles of C. nutans extracts in regulating macrophage cellular response in J774.2 mouse macrophages were investigated in this study as it can potentially provide benefits to patients with macrophage related inflammatory diseases as well as to patients with severe macrophage related immunodeficiencies. The macrophage cell line was characterised through morphological observation under inverted phase contrast microscope and expression of a few novel macrophage markers (CD11b, F4/80, CD80 and CD86) using flow cytometric analysis (FACS). The cytotoxicity effect of C. nutans leaves ethanol (EtOH), ethanol-aqueous (EtOH-AQ) and aqueous (AQ) extracts on J774.2 macrophages was determined using PrestoBlue assay. The secretion of a mixture of pro- and anti-inflammatory cytokines by the macrophages after 48 hours of extracts incubation was assessed using multiplexed cytokine bead-based assay.